Collegiate athletes opinions regarding helmet use while riding scooters or mopeds. Issue 7 (3rd October 2022) - Olewinski, Luci; Brooks, M. Alison; Wilson, John; Heidel, R. Eric; Watson, Andrew
Abstract: Many collegiate athletes use scooters and mopeds for transportation, and they are at greater risk for head injury without helmets. Objective: Investigate college athletes' reasons for wearing/not wearing helmets while riding a scooter or moped. Participants, Methods: 125 Division I athletes across five teams (two with helmet mandates) completed a cross sectional survey on rates and attitudes about helmet use on scooters or mopeds. Results: Helmet use on mandated vs non-mandated teams was 100% vs 3.6% (OR 1141; 95% CI 56.97, 22, 850). For the question, "if you do not wear a helmet, what might make you change your mind and wear one?", players most commonly wrote in a law or coaches' rule (57%). Conclusions: A coach's rule is associated with a higher rate of helmet use in collegiate athletes, and athletes primarily report a rule or law as the reason they would wear a helmet on a scooter or moped.